2021
DOI: 10.3389/fneur.2021.662497
|View full text |Cite
|
Sign up to set email alerts
|

Gout Is Not Just Arthritis: Abnormal Cortical Thickness and Structural Covariance Networks in Gout

Abstract: Background: Hyperuricemia is the cause of gout. The antioxidant and neuroprotective effects of uric acid seem to benefit some patients with central nervous system injury. However, changes in the brain structure have not been discovered in patients with gout.Object: Clarify the changes in cortical thickness in patients with gout and the alteration of the structural covariance networks (SCNs) based on cortical thickness.Methods: We collected structural MRIs of 23 male gout patients and 23 age-matched healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Serum UA levels above the upper reference range (i.e., hyperuricemia) are associated with gout [16], arterial hypertension [17,18], and metabolic syndrome [19], among others, and have a potentially negative impact on cortical thickness [16] and on the cerebrovascular status [20]. There is epidemiological evidence that lower levels of serum UA and U are associated with an increased risk of PD; this was shown in two large prospective studies [21,22], four case-control studies [23][24][25][26], and a cross-sectional study [27].…”
Section: Introductionmentioning
confidence: 99%
“…Serum UA levels above the upper reference range (i.e., hyperuricemia) are associated with gout [16], arterial hypertension [17,18], and metabolic syndrome [19], among others, and have a potentially negative impact on cortical thickness [16] and on the cerebrovascular status [20]. There is epidemiological evidence that lower levels of serum UA and U are associated with an increased risk of PD; this was shown in two large prospective studies [21,22], four case-control studies [23][24][25][26], and a cross-sectional study [27].…”
Section: Introductionmentioning
confidence: 99%
“…In a Mendelian randomization study of gout and brain volume, researchers found that genetically predicted gout was signi cantly associated with gray matter volume in the whole brain, and genetically predicted hyperuricemia was also signi cantly correlated with gray matter volume in several regions, including the cerebellum, midbrain, pons, and brainstem [32] . Compared with this previous study, our study provides a more detailed delineation of brain regions, further revealing the correlation between gout and the more subtle brain regions of the Left Frontal Operculum Cortex and Left Precentral Gyrus.Furthermore,Yang et al, in an imaging study using MRI technology to detect cortical volume in gout patients, found that the cortical thickness in the left upper frontal lobe region of gout patients was thinner than that of the healthy control group [33] . This nding is similar to the genetic prediction in our study that gout can cause a decrease in the volume of the Left Frontal Operculum Cortex.…”
Section: Discussionmentioning
confidence: 99%